2021
DOI: 10.1002/ctm2.265
|View full text |Cite
|
Sign up to set email alerts
|

Reiterative infusions of MSCs improve pediatric osteogenesis imperfecta eliciting a pro‐osteogenic paracrine response: TERCELOI clinical trial

Abstract: TERCELOI clinical trial addresses fundamental issues concerning the feasibility, security and potential of 5 MSCs infusions in two non immunosuppressed Osteogenesis Imperfecta pediatric patients. This trial allowed us to elucidate the mechanism of action of MSCs therapy, characterized by a pro-osteogenic paracrine response. For that, we studied the protein and miRNA levels in sera from patients (collected before, along and after the cell treatment) besides unraveling the transcriptomic alterations due to those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 67 publications
1
39
0
Order By: Relevance
“…During the clinical trial, both patients showed a reduction in bone fractures, as well as improvements in bone-related parameters and quality of life. Moreover, the study of the mechanism of action indicated a pro-osteogenic paracrine response in patients’ serum as a consequence of cell infusions, thus, reinforcing the hypothesis that MSCs elicit their beneficial effects, at least in part, through paracrine mechanisms [ 161 ].…”
Section: Strategies Promoting Bone Healing Through Exogenous Responsementioning
confidence: 75%
“…During the clinical trial, both patients showed a reduction in bone fractures, as well as improvements in bone-related parameters and quality of life. Moreover, the study of the mechanism of action indicated a pro-osteogenic paracrine response in patients’ serum as a consequence of cell infusions, thus, reinforcing the hypothesis that MSCs elicit their beneficial effects, at least in part, through paracrine mechanisms [ 161 ].…”
Section: Strategies Promoting Bone Healing Through Exogenous Responsementioning
confidence: 75%
“…We read with great interest the recent research article by Infante and colleagues, 6 where they have addressed the…”
Section: Commentarymentioning
confidence: 99%
“…Thus, the disease stage/severity of each patient, such as immune status, hypoxia, inflammation or extracellular matrix alterations, can affect the therapeutic outcomes of MSCs [ 9 ]. Along these lines, our recent clinical trial assessing repetitive HLA-matched young MSC infusions in two pediatric patients affected by the rare bone disorder osteogenesis imperfecta reported better beneficial outcomes, and systemic pro-osteogenic response in the most severely affected patient [ 13 ].…”
Section: Future Directions and Conclusionmentioning
confidence: 99%
“…Along these lines, the first studies using MSCs as a therapy in pediatric patients affected by the rare bone disorder, osteogenesis imperfecta, showed that after in vivo administration, the engraftment of MSCs in target tissues such as bone was anecdotal, although beneficial effects were found [ 11 ]. A growing body of evidence points to the secretory properties of MSCs as the underlying mechanisms behind the beneficial effects of MSCs-based therapies, rather than the initial cell replacement that MSCs were supposed to exert [ 11 , 12 , 13 ]. This assumption is supported by the fact that the active components secreted by MSCs, mainly exosomes, are themselves demonstrating efficacy as cells to treat certain pathologies [ 14 ].…”
Section: Introductionmentioning
confidence: 99%